2020
DOI: 10.1002/ece3.6095
|View full text |Cite
|
Sign up to set email alerts
|

Stable resource polymorphism along the benthic littoral–pelagic axis in an invasive crayfish

Abstract: Although intraspecific variability is now widely recognized as affecting evolutionary and ecological processes, our knowledge on the importance of intraspecific variability within invasive species is still limited. This is despite the fact that understanding the linkage between within‐population morphological divergences and the use of different trophic or spatial resources (i.e., resource polymorphism) can help to better predict their ecological impacts on recipient ecosystems. Here, we quantified the extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 78 publications
(135 reference statements)
0
15
0
Order By: Relevance
“…Faxonius limosus is also known to experience two peaks of mating activity throughout the year with long‐term storage of sperm (Aklehnovich & Razlutskij, 2013; Buřič et al., 2013; Holdich & Black, 2007). In the studied system, previous works highlighted the existence of substantial phenotypic variability (morphology, trophic ecology) among (Evangelista, Lecerf, et al., 2019; Jackson et al., 2017) and within populations of P. clarkii (Lang et al., 2020; Raffard et al., 2017). This suggests contrasting impacts of invasive individuals on ecosystem functioning among populations of P. clarkii (Alp et al., 2016; Evangelista, Lecerf, et al., 2019).…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…Faxonius limosus is also known to experience two peaks of mating activity throughout the year with long‐term storage of sperm (Aklehnovich & Razlutskij, 2013; Buřič et al., 2013; Holdich & Black, 2007). In the studied system, previous works highlighted the existence of substantial phenotypic variability (morphology, trophic ecology) among (Evangelista, Lecerf, et al., 2019; Jackson et al., 2017) and within populations of P. clarkii (Lang et al., 2020; Raffard et al., 2017). This suggests contrasting impacts of invasive individuals on ecosystem functioning among populations of P. clarkii (Alp et al., 2016; Evangelista, Lecerf, et al., 2019).…”
Section: Methodsmentioning
confidence: 84%
“…For each species, crayfish abundance was estimated in each lake as the number of individuals trapped over 24 hr (catch per unit effort expressed in ind trap −1 hr −1 ; Table 1). The predation pressure in each lake was assessed as the biomass of predator fish trapped in a set of gillnets randomly distributed, over 1 hr (biomass per unit effort expressed in g gillnet −1 hr −1 ; Table 1; see further details in Lang et al., 2020 and Zhao et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no documented impacts have been reported on the ecosystem in Martinique, invasive crayfish are known to have profound impacts on freshwater communities (plants and animals) due to their opportunistic, omnivorous and predatory nature. This can affects the trophic chain at all levels, by competing with autochthonous species or predating them and perturbating the entire ecosystem functioning (Loureiro et al, 2015;Jackson et al, 2017;Lang et al, 2020). For example, several studies have shown that P. clarkii (Jackson et al, 2014;Loureiro et al, 2015;Lang et al, 2020), P. leniusculus (Jackson et al, 2014;Vaeßen and Hollert, 2015) and Faxonius virilis (formerly Orconectes virilis) (Jackson et al, 2014) can cause strong decreases in species richness of insect larvae and mollusks through predation after their introductions to a new location.…”
Section: Geographic Distribution Of the Haplotypesmentioning
confidence: 99%
“…This can affects the trophic chain at all levels, by competing with autochthonous species or predating them and perturbating the entire ecosystem functioning (Loureiro et al, 2015;Jackson et al, 2017;Lang et al, 2020). For example, several studies have shown that P. clarkii (Jackson et al, 2014;Loureiro et al, 2015;Lang et al, 2020), P. leniusculus (Jackson et al, 2014;Vaeßen and Hollert, 2015) and Faxonius virilis (formerly Orconectes virilis) (Jackson et al, 2014) can cause strong decreases in species richness of insect larvae and mollusks through predation after their introductions to a new location. Studies also suggest a decrease in the abundance and diversity of aquatic plants and animals is directly related to crayfish density (Gherardi and Acquistapace, 2007;Rodríguez-Pérez et al, 2015).…”
Section: Geographic Distribution Of the Haplotypesmentioning
confidence: 99%